Laser welding of aluminium alloys 5083 and 6082 under conduction regime - Sánchez-Amaya, José Maria; Delgado-Pérez, Tomás; González-Rovira, L.; Botana, F.J. (Elsevier, 2009)
In this work, samples of aluminium alloys 5083-T0 and 6082-T6 have been welded under conduction regime, using a high power diode laser. The influence of experimental variables, as the laser power and the linear welding rate, on the sizes and properties of the butt weld beads has been studied. In addition to measure the depths and widths of the weld beads, their microstructure, microhardness profile and corrosion resistance have been analysed. The results obtained allow one to define the experimental conditions leading to good quality butt welds with higher penetration than those published in the recent literature under conduction regime. Maximum penetration values of 3 and 2.3 mm were obtained for 5083 and 6082, respectively. Additionally, a simple mathematical expression relating the weld depth (d) with the laser power (P) and the processing rate (v) has been proposed: d = (P - bb)/ (av) - (ba)/a, beinga, a0, b and b0 constant values for each alloy and under the employed experimental conditions. The values of these coefficients have been estimated from the fitting to the experimental depth values of 5083 and 6082 butt welds generated under conduction regime.
Keywords: Fusión con laser; Soldeo - Defectos; Laser welding; Aluminium alloys; Conduction regime; depth estimation; Corrosion resistance